Grounding perceptions: the value of otoendoscopy images in strengthening parents and children's understanding and decision making in a pediatric ENT clinic - Carter, Bernie; Hampton, Thomas; Sharma, Sunil; De, Sujata (Frontiers in Communication, 2023)
Introduction In recent years, there has been an increasing use of otoendoscopy in middle ear surgery. There is also increasing evidence of its usefulness as a diagnostic tool for clinicians. However, there is limited evidence on whether understanding their ear condition is of benefit to patients. This novel study sought to explore the perceptions, perspectives, and satisfaction of parents, children, and young people regarding the use of otoendoscope images in outpatient ENT consultations in relation to their understanding of ear symptoms, disease, and subsequent treatment. The framework for the study is child (and parent) health literacy and how visual images can play in scaffolding understanding, communication, and decision-making. Methods This qualitative descriptive exploratory study used semi-structured observation, a survey, short conversational interviews, and child activities. Results Purposive sampling of 16 children (aged 4–15 yrs, various diagnoses) and parents/carers attending an outpatient ENT clinic at a tertiary pediatric hospital. One overarching theme, “Grounding perceptions and deepening engagement,” and two sub-themes, “Strengthening understanding” and “Supporting decision-making,” were identified. The children and parents valued the opportunity to see the images and gain insight and knowledge of their child's pathology. Discussion The images appeared to promote child (and parent) health literacy and interaction between the child-parent-clinician and informed shared decision-making. This study suggests that the use of otoendoscopy in an out-patient setting and sharing of the images with parents, children, and young people have a largely positive impact on understanding, relationship building, and decision making in pediatric ENT consultations.